Strategi Pemasaran Digital Dalam Meningkatkan Penjualan Pada Thrifting Panorama Kota Bengkulu - Andini, Puja; Soleh, Ahmad; Irawan, Yudi; Sudarsono, Aji; Ertanto, Dodi (Jurnal Dehasen Untuk Negeri, 2024)
This research aims to explore digital marketing strategies that can be implemented to increase sales at the thrifting shop in Panorama, Bengkulu City. By utilizing social media and e-commerce platforms, it is hoped that thrifting business actors can increase market reach and income. The research methods used were surveys and interviews with Ms. Elytha as a thrifting business actor as well as analysis of sales data before and after implementing digital strategies. The research results show that effective use of social media and e-commerce can increase sales by up to 30%. The conclusion of this research is that digital marketing strategies have great potential to be implemented in thrifting businesses in Bengkulu. The challenge faced is tight competition between business actors who use the same digital marketing strategy.